Le pouvoir laïque est-il profane ? Classement distinctif et spiritualisation seigneuriale en Haute-Allemagne à la fin du Moyen Âge - Joseph Morsel; Camille Noûs (Bulletin du Centre d’Études Médiévales d’Auxerre)
The burial of the dead in churches is a practice specific to medieval society, unthinkable in ancient Rome and forbidden in contemporary society. It is not, however, simply a variant of the ad sanctos burial, in that it is frequently manifested by the existence of a more or less ornate sepulchre, making the defunct visible in the church. Initially reserved for clerics and founders of ecclesiastical establishments, this practice became more widespread from the 12th century onwards. Having one’s tomb in a church is generally interpreted either in religious terms – piety, fear of death a.s.o. –, or as a form of social distinction – generic arguments that fail to consider the medieval system of representation. The article proposes a different interpretation of this practice, starting from a specific empirical terrain – secular lords in Upper Germany in the late Middle Ages – and considering seriously the caro/spiritus schema – instead of the common, albeit dated profane/sacred binomial couple –, not only as a discursive system but also and above all as the actual ideational matrix of social practices. We can then deduce the generic correlation established in this society between social – secular as well as ecclesiastical – domination and the attribution of a more spiritual character to the dominant than to the dominated, who are relegated to the carnal.